2015
DOI: 10.3399/bjgp15x686053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical history for diagnosis of dementia in men: Caerphilly Prospective Study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…We previously found that the diagnostic accuracy of simple questions concerning functioning and independent living was comparable to longer more established measures of cognitive functioning in a group of men who had been screened for cognitive problems [ 40 ]. Here we describe a prospective study to evaluate the accuracy of a range of tests for diagnosing dementia in a primary care setting.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that the diagnostic accuracy of simple questions concerning functioning and independent living was comparable to longer more established measures of cognitive functioning in a group of men who had been screened for cognitive problems [ 40 ]. Here we describe a prospective study to evaluate the accuracy of a range of tests for diagnosing dementia in a primary care setting.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the absence of a negative impact of our intervention on mental health, and on the favorable experiences of the FPs and PNs, we would recommend not to be overly careful to discuss and to assess whether or not older persons have cognitive deficits. Based on the comparison of the CAMCOG results with the PNs’ screening results, presently used cognitive tests on their own appear insufficient for the initial detection of (earlier stages of) cognitive decline; we would recommend that initial assessments include a careful history, proxy history and an assessment of functioning [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GPCOG also asks particularly about difficulties with managing medications, finances, and gadgets as there is evidence that people with dementia may struggle with these tasks. 8 , 9 Younger patients (<70 years) with symptoms that are acknowledged by an informant present a particular challenge, and in practice the authors would exclude affective disorder and then have a low threshold for seeking advice. For older people (>90 years) with multimorbidity (for example, in a nursing home) it might be more appropriate to focus on managing distress and advance care planning.…”
Section: So What Should the Busy Gp Do?mentioning
confidence: 99%